O Gnaisse alcalino de Serra do Matola - São Jõao Del Rei (Boletim da Faculdade de Filosofia, Ciências e Letras da Universidade de São Paulo. Mineralogia, 1968)
This paper deals wTh the so-called Serra do Matola alkaligneiss, emphasizing its geologic and pétrographie characters. This alkaline formation situated south of São João Del Rei, Minas G era’s, Brazil has a N-S elongated shape, with a length of about 20 km and an area of 100 km 2, approximately The bed rock outcrops in small areas totaling 20.000 m2, mainly in the escarpments facing north. Bounding the alkali-gneiss sierra, one can find charnockit ’c gneisses to the east and the Piedade biotite-gneiss to the west both of which can be inferred to contact each other underneath the alkali-gneiss. The planar structure as well as contacts between alkali gneisses and biotite gneisses are sub horizontal and somewhat irregular, but the general dip is to the south. A sometimes strong lineation can be observed in the alkali gneiss trending around 24°W and plunging 8°S. In this formation, field evidences indicate EW movements but there are also subordinate thrust faults SN. A system of vertical shearing planes runs NE-SW and NW-SE. The charnockites are much more irregular and seem structurally independent from the alkali and biotite-gneiss. The general characters of the alkah-gneisses are: 1) undeformed, fine-grained, leucocratic; mafic minerals concentrated in dark zones, here called “shonkinitic gneiss”; 2) granular quartz in strings or scattered. Porphyroblasts of feldspar, aegirite-augite and titanite. Potassic feldspar: microcline (Ab20) showing variable perfection of grid twinning, probably related to the variable reticular obliquity, which in turn would be related to the temperature of its formation (always below 5f00°C). Plagioclase is albite (An7) seldom twinned and never zonned, indicating total metamorphic re crystallization. Piroxene: aegirite-augite averaging 10% of the Na molecule. Amphibole: hastingsite. Common accessories: titanite, magnetite, apatite, epidote, allanite and calcite. Biotite, zircon and andradite are very scarse. Allanite, which is responsable for the radioactivity in the gneiss, may be found partially metamictized: it sometimes substitutes for titanite or envelops apatite. The average content of T h 0 2 in the rock is 0.015%, but allanite — and consequently T h 0 2 — may be abnormally concentrated in certain melanocratic (shonkinitic) levels. 3) Both the chemical analysis and the chemical variation diagram of the rock show similarities to correspondent data for rocks considered as final products of magmatic differentiation, namely trachytes and alkali rhyolites (pantellerites). On this basis, the alkali gneiss is believed to be the product of regional metamorphism acting upon an alkaline efusive rock. The melanocratic layers may have come from basic differentiated magmas also m etam orphised. Regional metamorphism affected the alkali gneiss which was stabilized in the same facies and sub-facies of the biotite gneiss (see b elo w ). The N-S structural lines are believed to be due — as the petrofabric analyses suggests r— to tectonic movements along an E-W direction with probable WE transport. The klkaline magma may have crystallized at high temperature, bringing about homogeneous Na-K feldspars. The metamorphism is believed to have promoted the unmixing of the Or and Ab molecules, shown now as indepent crystals in the fine grained m atrix and as perthitic porphyroblasts. A t the same time the sodic pyroxene would turn to hastingsite. The general characters in the Piedade biotite-gneiss are: 1 — Undeformed fine to medium grained mesocratic rock, rich of biotite in preferred orientation. Pegmatitic venulation, microcline porphyroblasts and metamorphic layering are observed in places. Recrystallization is widespread but here and there a psammitic relict texture can be guessed. 2 — The plagioclase is the commonest mineral. It is unzonnsd and is scarsely twinned but shows a somewhat variable An content from sample to sam ple. A calculated average gives A n2i. Quartz, very much abundant here, and microcline, are closely comparable to their counterparts in the alkali gneiss. Lepidoblastic biotite is to be found in any thin section. Other minerals present include: muscovite, epidote, titanite, magnetite, apatite, zircon and garnet. 3 — Chemically the rock is comparable to the series granite-diorite or arkose-grayw acke. Taking into account the texture it is supposed that it evolved from a clastic graywackic sediment. Mineralogic analysis show that it was stabilized in the staurolite-almandine or kyanite-almandine-muscovite subfacies of the almandine amphibolite facies. The petrofabric simmetry analysis parallels those obtained in the study of the alkali gneiss, i.e. the N-S macro and microlineation would be due to a E-W movement. The general characters in the charnockitic rocks are: 1 — Dark, basic, medium grained, and entirely recrystallized rocks are represented by amphibolites and pyroxene-granu lites. Lighter colored, acid, coarse grained, essentially quartz feldspathic rocks are here called acid chamockites. There are intermediate types. 2 — The acid charnockites are made up of quartz, abundant orthoclase perthite and oligoclase antiperthite, hypersthene, diopside and some biotite. Pyroxene-granulites contain andesine or bytownite, hypersthene and diopside. Amphibolites are characterized by the andesine-hornblende association, the last mineral being the greenish brown variety relatively oxydised and anhydrous. In the amphibolites some red biotite and /or garnet may have formed by retrom etam orphism . No titanite or sphene were seen in thin-sections. There is a simpathetic relation in the Fe content between the two pyroxenes present in the charnockite series of rocks. 3 — The acid charnockites seem to have been palingenetically mobilized magmas. The pyroxene-granulites and amphibolites could well represent supra crustal rocks led to plu tonic environment, where they were metamorphised in the two sub-facies (hornblende-, pyroxene-) of the granulite facies. A previous author stated that the region in study was subjected to a SN thrust tectonism. This conclusion is not invalidated by the present author but it is suggested that the thrusts moved large sheets of hard rocks carrying the printed fabric imposed by an earlier dynamic phase. Mineralogical radiometric analysis were carried on concentrated sam ples. It was concluded that the mineral responsable for the radioactivity in the sane gne’ss is allanite and in the residual so’l mantle, an amorphous thorogumite